2008
DOI: 10.1152/japplphysiol.00075.2008
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced obesity causes innate airway hyperresponsiveness to methacholine and enhances ozone-induced pulmonary inflammation

Abstract: Johnston RA, Theman TA, Lu FL, Terry RD, Williams ES, Shore SA. Diet-induced obesity causes innate airway hyperresponsiveness to methacholine and enhances ozone-induced pulmonary inflammation. J Appl Physiol 104: 1727-1735, 2008. First published March 6, 2008 doi:10.1152/japplphysiol.00075.2008.-We previously reported that genetically obese mice exhibit innate airway hyperresponsiveness (AHR) and enhanced ozone (O3)-induced pulmonary inflammation. Such genetic deficiencies in mice are rare in humans, and they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(113 citation statements)
references
References 70 publications
8
98
1
4
Order By: Relevance
“…Previous work has suggested that obesity may have an attenuating effect on hyperoxic and ozone-induced lung injury models, although in the case of ozone exposure findings are mixed and appear to vary with the acuity of exposure and possibly the timing of examination (22,32,33). These findings, in light of the early evidence that obesity may have a protective effect in human ALI/ARDS (7,34,35), suggest that a clinically relevant alteration in the acute pulmonary inflammatory response may be associated with weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has suggested that obesity may have an attenuating effect on hyperoxic and ozone-induced lung injury models, although in the case of ozone exposure findings are mixed and appear to vary with the acuity of exposure and possibly the timing of examination (22,32,33). These findings, in light of the early evidence that obesity may have a protective effect in human ALI/ARDS (7,34,35), suggest that a clinically relevant alteration in the acute pulmonary inflammatory response may be associated with weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Obese mice fed a high-fat diet develop increased airway reactivity only after a certain age and weight: for example, 20-to 22-week-old C57BL/6 mice (average weight, 43 g) fed a high-fat diet did not have increased airway reactivity compared with mice fed a low-fat diet, whereas 30-to 38 week-old-mice (average weight 50 g) did (19). These results suggest that an interaction between aging and weight gain may contribute to the inherent airway reactivity of obesity, and more studies on this are needed in humans.…”
Section: Asthma Caused By Obesitymentioning
confidence: 99%
“…Largely through the work of Shore et al, molecular and physiologic characteristics of the murine model of obese asthma are currently being elucidated. 23,[26][27][28][29][30][31][32][33][34] However, assessing lung inflammation and lung responses among obese children remains challenging and limited by current technologies. Studies in children involving bronchodilator responsiveness, bronchoconstricting agonists (e.g., methacholine challenge), and airway inflammatory markers have yet to show the same consistent pattern of hyperresponsiveness that have been demonstrated in mice.…”
Section: If Obesity Leads To Asthma What Is the Mechanism?mentioning
confidence: 99%